Preparation of Cisplatin Loaded Gelatin Nanoparticles by Glutaraldehyde Crosslinking; Evaluation of Mechanism of Crosslinking and Involvement of Cisplatin in the Crosslinking Process - Balaji, Anna; Pandey, V.P.; Srinath, M.S.; Manavalan, R. (Asian Journal of Chemistry, 2010)
Cisplatin (cis-dichlorodiammineplatinum(II), CDDP) is a commonly used chemotherapeutic agent for treatment of various cancers, including testicular cancer, ovarian cancer, lymphoma and glioma. To counteract resistance, clinical dosing is increased which leads to renal toxicity, late neurotoxicity as well as ototoxicity, nausea and vomiting. Gelatin nanoparticles encapsulating cisplatin were produced using a two-step desolvation technique using glutaraldehyde as the crosslinking agent to increase drug concentration in cancer tissues with fewer side-effects. Glutaraldehyde is a highly reactive and efficient crosslinking agent whose mechanism of crosslinking is based on intra-particulate bridging of residual amino groups present in gelatin. Also the possible involvement of primary amino groups of cisplatin in the crosslinking process was investigated. The size of nanoparticles was around 223 to 324 nm and the entrapment efficiency was found to be 35.6 %. Crosslinking studies revealed that cisplatin loaded nanoparticles showed a greater number of free amino groups than plain gelatin nanoparticles indicating possible competition between the amino groups of cisplatin and amino groups of gelatin polymer during the crosslinking process. The possibility of binding of amino groups of cisplatin with the amino groups of gelatin via glutaraldehyde was confirmed by thin-layer chromatography. In vitro studies showed an initial burst release of cisplatin (22.42 %) followed by gradual and incomplete drug release up to 72 h in PBS pH 7.4. Enzymatic disruption of protein matrix with trypsin further released 9.7 % of the drug and remaining drug corresponds to cisplatin which is covalently linked to amino groups of gelatin.